Effect of Sesbania rostrata Liquid Green Manure and Gypsum at Water Content in Sodic Soil and Plant Growth of Solanum torvum - Erwin Junaidi Lubis (CV Projurnal Mitra Publikasi, 2025)
Sesbania rostrata is a plant classified as leguminoceae which has nodules on the roots. Nodules on the roots contain Rhizobium bacteria that can tether N2 from the air and are able to convert large amounts of atmospheric nitrogen into plant-available nitrogen. Gypsum fertilizer is a fertilizer containing calcium (Ca) and sulfur (S) derived from the mineral gypsum and the benefits of gypsum can increase plant growth, improve soil physical and chemical properties, and improve plant roots. This study aims to determine the effect of liquid green manure from Sesbania rostrata and gypsum on the growth of Solanum torvum plants on the physical and chemical properties of the soil, as well as the provision of water content in sodic soil that accumulates gypsum and Sesbania rostrata liquid green manure. This research used Randomised Group Design (RGD) with 4 repetitions. This research was conducted for 4 months. The experimental parameters observed consisted of saturated soil moisture content, field capacity moisture content, soil content weight, soil cation exchange capacity (CEC), soil porosity, soil plasticity index, soil electrical conductivity, and exchangeable calcium. The application of gypsum and Sesbania rostrata liquid green manure significantly affected saturated water content, field capacity water content, soil content weight, soil electrical conductivity, and vegetative plants but not significantly different on cation exchange capacity (CEC) and soil porosity.